2021
DOI: 10.3390/cells10071682
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Treatment Improves Renal Fibrosis via miR-4516/SIAH3/PINK1 Axis

Abstract: Dysregulation in mitophagy, in addition to contributing to imbalance in the mitochondrial dynamic, has been implicated in the development of renal fibrosis and progression of chronic kidney disease (CKD). However, the current understanding of the precise mechanisms behind the pathogenic loss of mitophagy remains unclear for developing cures for CKD. We found that miR-4516 is downregulated and its target SIAH3, an E3 ubiquitin protein ligase that reduces PINK1 accumulation to damaged mitochondria, is upregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…There is an increasing number of studies have demonstrated the potential mechanisms of ncRNA-regulated mitochondrial dynamics. Chen et al, 2015;Costa et al, 2013;Yoon et al, 2021). Thus, further research is warranted on the role of ncRNAs as a putative therapeutic target in the treatment of diabetes and its complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is an increasing number of studies have demonstrated the potential mechanisms of ncRNA-regulated mitochondrial dynamics. Chen et al, 2015;Costa et al, 2013;Yoon et al, 2021). Thus, further research is warranted on the role of ncRNAs as a putative therapeutic target in the treatment of diabetes and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is worth investigating the participation of mitophagy in diabetes and its complications and the possibility of mitophagy as a potential therapeutic target. Finally, previous research on miRNA pharmacogenomics has demonstrated that miRNAs can affect the efficacy of the drug via downregulating gene expression that is essential for drug functions (S. M. Chen et al, 2015; Costa et al, 2013; Yoon et al, 2021). Thus, further research is warranted on the role of ncRNAs as a putative therapeutic target in the treatment of diabetes and its complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can regulate the activity of the members of the MMP family, which is involved in remodeling the endometrium, thereby alleviating the progress of the epithelium in endometriosis 7,8 . In addition, melatonin has an antifibrotic effect in renal tissue, which improves mitochondrial homeostasis and prevents uterine horn‐induced intraperitoneal adhesion in a rat model 9,10 . Therefore, melatonin supplementation could restore the physiological function of the uterus to its normal state.…”
Section: Introductionmentioning
confidence: 99%